pola komunikasi guru dengan anak keterbelangan mental di YYPC Banda Aceh - Sahputra Sahputra; Nurhasanah Nursahanah; Martunis Martunis (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2017)
ABSTRACT  Sahputra. 2017. Communication Patterns Teachers and Children's Mental Backwardness to YPPC Banda Aceh. Skripsi, Departement of Guidance and Counseling,The Faculty of Teachers Trainning and Education,Syiah Kuala University Supervisor:(1)   Dra. Nurhasanah, M.Pd., (2) Drs. Martunis, M.Si. Keywords: Communication Patterns, Teachers, Children's Mental BackwardnessBasically, communication is needed by everyone, either normal or people with special needs such as children who have mental retardation. Communication patterns greatly affect the existence of persons with mental retardation in doing habit. Children with mental retardation overall retarded growth and weakness in the psychological field. This study aims to determine the communication pattern teacher with child mental retardation and obstacles encountered in the process of communication in Banda Aceh YPPC. This study used a qualitative approach. The subjects were 4 teachers. The object of research is the communication pattern teacher with mentally retarded children. Data is collected using interviews, observation and documentation. The results showed that the communication pattern teacher with mental retardation in the child YPPC Banda Aceh is a pattern of two-way communication occurs reciprocal (feedback) between teachers and students, but not balanced in the communication process to respond to what you want to say by the child and give the child a positive appreciation of the initiative storytelling and develop empathetic communication. In practice, the patterns of communication between teachers and children take place relatively good mental retardation. Obstacles faced by teachers, among others, misperceptions between teachers and students in the communication process of learning as children grow and develop, so that his curiosity was sometimes greater. As for his mental development is not balanced in the process of communication with teachers. In addition, other constraints that teachers face is difficult to change the mindset mainset or students to be more successful in the learning process.